Clinical and Trichoscopic Evaluations of Topical Finasteride 1%, Topical Spironolactone 5%, and Minoxidil 5% in Female Pattern Hair Loss Treatment - Naglaa Mohamed El Sayed; Eman Hamed Elmorsy; Tarek Mahmoud Hussein; Eman Hassan (Dermatology Practical & Conceptual)
Introduction: Female pattern hair loss (FPHL) is one of the most common forms of diffuse alopecia in females.. Despite the availability of multiple treatment options, FPHL management poses challenges for the dermatologist.